Patterns of Labour Market Entry of High-Skilled Workers in Germany - Mario Reinhold; Stephan Thomsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Recent evidence for the US labour market indicates that despite supply of higher skilled job market entrants rose, there was a (permanent) decline in demand for those qualifications in the aftermath of the Tech Bust in 2000. Since Germany experienced also an increase in high-skilled labour supply, and both economies depend on similar factors, we analyse the corresponding situation of the demand-supply relation. Based on data of the German SocioEconomic Panel Study (GSOEP) for the years 1984 to 2012, we present long-run wage and occupational trends of the increasing number of labour market entrants with higher education. The results indicate that job entrants with a university (postgraduate) degree have faced steadily high occupational shares in the cognitive sector accompanied with high and increasing wages. Job market entrants from college or universities of applied sciences, however, experienced a decline in employment shares in the cognitive sector associated with declining wages. The provided evidence shows that occupational success of university graduates is heterogenous with distinct and different patterns for the high and highest educated.
Keywords: J21; J23; O33; 330